2016
DOI: 10.1002/adma.201603560
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Microgap in Iridescent Cellulose Nanocrystal Films

Abstract: A new photonic structure is produced from cellulose nanocrystal iridescent films reflecting both right and left circularly polarized light. Micrometer‐scale planar gaps perpendicular to the films' cross‐section between two different left‐handed films' cholesteric domains are impregnated with a nematic liquid crystal. This photonic feature is reversibly tuned by the application of an electric field or a temperature variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 37 publications
4
176
1
2
Order By: Relevance
“…Cellulose nanocrystals were obtained from the acid hydrolysis of microcrystalline cellulose (MCC; Aldrich Avicel®,~50 µm particle size, derived from cotton) with sulphuric acid (Sigma-Aldrich, 95-97% purity), as described elsewhere by Fernandes et al [25], however a reaction time of 40 min instead of 130 min was used. A lower reaction time was selected since the authors confirmed that the particles produced by these conditions were very similar to the ones synthesized using longer reaction times.…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose nanocrystals were obtained from the acid hydrolysis of microcrystalline cellulose (MCC; Aldrich Avicel®,~50 µm particle size, derived from cotton) with sulphuric acid (Sigma-Aldrich, 95-97% purity), as described elsewhere by Fernandes et al [25], however a reaction time of 40 min instead of 130 min was used. A lower reaction time was selected since the authors confirmed that the particles produced by these conditions were very similar to the ones synthesized using longer reaction times.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Cellulose nanocrystals (CNCs) are an excellent example of such a biosourced nanomaterial, owing to a unique combination of chemical, mechanical, and optical properties, [2,3] which explains the increase of interest in this system for applications as pigments, [4] security coatings, [5,6] sensing or responsive materials, [7][8][9][10][11][12] and mesoporous chiral nanotemplates. Such approaches can offer a cost-effective and scalable solution to design materials with a desired optical response.…”
Section: Nanocrystal Filmsmentioning
confidence: 99%
“…Because of the negative sulfate half-esters or other surface charges remaining from the production procedure, CNCs are easily dispersed in water. Adding their excellent mechanical properties, optical transparency, ease of chemical functionalization, and ability to form a longrange-ordered LC phase, CNCs are highly attractive for the realization of tunable, in some cases even responsive, highperformance materials with spectacular mechanical and optical properties 5,9,[13][14][15] . The LC phase formed by CNC suspensions is of the chiral nematic, or cholesteric, type.…”
Section: Introductionmentioning
confidence: 99%